Willingness, motivators and barriers to time bank participation: A scoping review - Nur Shafira Azizan; Chong Chin Che; Mei Chan Chong; Maw Pin Tan; Yong Kek Pang; Khadijah Alavi (PLoS ONE, 2026)
This scoping review systematically identifies the extent and nature of evidence regarding willingness, motivators, and barriers influencing community participation in time bank systems, with a focus on older adults. Time bank is recognized as an effective tool for enhancing social cohesion and reducing isolation, particularly among older adults. However, specific factors such as barriers and motivators driving participation remain underexplored. This review adhered to Arksey and O’Malley’s framework and PRISMA-ScR guidelines. A systematic search of PubMed, Embase, CINAHL, Web of Science, Cochrane Library, Google Scholar, and Science Direct (January 2010–December 2024) identified studies on willingness, motivators, and barriers to time bank participation. Two reviewers independently screened titles, abstracts, and full texts, extracting data using a predefined tool. Thirty studies (quantitative, qualitative, and mixed-methods) were included. Findings revealed high willingness among younger populations, particularly university students, driven by intrinsic motivations like altruism and meaningful engagement. Healthcare professionals and older adults showed moderate willingness, influenced by health needs and caregiving roles. Key motivators included robust willingness to participate across different population, social and community influences, demographic and structural determinants, institutional and organizational support. Barriers included psychological and perceptual barriers, structural and systemic barriers, technological and usability, social and community, economic and policy-related barriers. Time bank holds significant potential for fostering community engagement, but challenges such as usability and trust must be addressed. Tailored strategies, improved platform design, and supportive policies are essential to maximize participation. Future research should address identified gaps to develop inclusive, scalable, and sustainable time bank systems that meet diverse community needs.